LEXICO-SEMANTIC REPRESENTATION OF THE PHILOSOPHICAL CATEGORY “LOVE” WITHIN THE FRAMEWORK OF THE SPACE-TIME CONTINUUM IN THE POETIC AND EPISTOLARY HERITAGE OF A.K. TOLSTOY - Burdina, E.A. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article is devoted to the study of the definition of “Love” based on the lexico-semantic aspect presented in the lyrics and letters of A.K. Tolstoy. The author investigates the lexemes included in the lexical semantic fields “Love”, “Time”, “Space”, revealing the semantic changes in their semantic structure which occur under the influence of the contextual environment. The lexico-semantic expression of the “chronotope of love” in the analyzed texts of the letters actualizes the local-temporal seme in the structure of lexemes that are not related to the semantics of space and time, which leads to the semantic variety of the A.K. Tolstoy’s epistolary. The representation of the philosophical category “Love” in the poet’s letters is compared with the lexical-semantic expression of this concept in the author’s poetry. The com-parison is made with the help of the dictionary article “Love” from the poetic vocabulary of A.K. Tolstoy’s language, which is currently under development, is used. The comparative analysis allows us to determine the relation of the main philosophical constants “time”, “space”, “movement” to the concepts of “love” and “God”, which are the semantic basis of texts of the letters and poetic works of A.K. Tolstoy. Such a study allows us to determine the range of the main lexical representatives of the “love chronotope” in the consid-ered fragment of the writer’s work, which details the linguistic picture of the author’s world and reveals the worldview of the elite language personality.